2016
DOI: 10.1007/s15010-016-0927-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial coinfections in dengue virus disease: what we know and what is still obscure about an emerging concern

Abstract: Despite the real burden and consequences of this emerging concern is still not computable accurately due to the lack of a significant number of studies on large cohorts, clinicians need a greater awareness about it to early recognize warning signs, to properly use available diagnostic tools and to readily start antibiotic treatment able to prevent worsening in mortality and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 50 publications
0
36
0
1
Order By: Relevance
“…The group also noted an important lack of trials focusing on some specific patient populations important to Asia-Pacific countries, such as tropical diseases [16][17][18][19][20][21][22][23][24][25][26]. Because of the lack of strong trial data currently limiting the clinical utility in these patients, there is need for adaptation of the proposed algorithms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The group also noted an important lack of trials focusing on some specific patient populations important to Asia-Pacific countries, such as tropical diseases [16][17][18][19][20][21][22][23][24][25][26]. Because of the lack of strong trial data currently limiting the clinical utility in these patients, there is need for adaptation of the proposed algorithms.…”
Section: Resultsmentioning
confidence: 99%
“…A drop in PCT from the peak by ≥80% and/or fall below the cut-off was taken as a strong indicator for resolution of illness, and earlier discontinuation of antibiotics is recommended when the patient is clinically stable. Discussing the application of the algorithms in the context of the Asia-Pacific patient population, it was emphasized that for patients with clinical suspicion of tropical diseases such as malaria, Dengue fever or hemorrhagic fever, and other diseases with high prevalence in the region, such as tuberculosis or typhus, there is a lack of systematic PCT studies in general and of antibiotic stewardship studies in particular [16][17][18][19][20][21][22]. There are some studies suggesting that PCT may help to risk-stratify these patients and provide prognostic information, but more research is needed to understand the role of PCT in these clinical conditions before applying PCT-guided antibiotic stewardship to them.…”
Section: Namementioning
confidence: 99%
See 1 more Smart Citation
“…Discussion A study in Singapore showed 0.3% prevalence of bacteraemia among adult patients with dengue and Staphylococcus aureus was the commonest pathogen 4 . Being critically ill at presentation, comorbidities, advanced age and more severe dengue manifestations are risk factors for bacteraemia in adults 4,5 . A study in Sri Lanka showed that 25% of adult dengue patients with fever lasting more than 5 days have bacteraemia 6 .…”
Section: Case Reportmentioning
confidence: 99%
“…Bacterial co-infection increases the morbidity and mortality of dengue. Bacterial co-infections are associated with 14.3-44.4% mortality 5 . Salmonella typhi co-infection was reported in a child with dengue fever in India 7 .…”
Section: Case Reportmentioning
confidence: 99%